Closing the loop with collegiate conversations in an Australian voluntary peer review of teaching program - Bolt, Susan; Perrin, Brian; Porter, Stacey (Common Ground, 2013)
In Australian universities, internal or external peer reviews are not mandatory or universally practiced. However, the regulatory framework is currently under review, and the newly appointed Australian Tertiary Education Quality and Standards Agency has indicated that peer assessment is an important element of quality. This paper focuses on the development of an internal voluntary peer review of teaching program, which was designed to support the professional development of teachers in a higher-education context. The purpose of this paper is to describe the processes developed to close the loop between observations, feedback, and identification of ongoing support strategies to improve the teaching and learning of the participating academics. An overview of relevant literature is provided to contextualise and differentiate this voluntary peer review of teaching program. To evaluate the program, quantitative and qualitative data were collected under ethics approval via a 38-question survey administered to all fifteen participants in 2010. Data were also collected through participant observation. In this paper, statistical and narrative information is provided pertaining to two key aspects of the program: identifying characteristics of the feedback loop and describing how it was closed. Instruments used to facilitate reflective practice and develop action plans for professional and career development, which are included, have implications for improvement of teaching practices, scholarship of teaching and learning, and career development. Findings presented in this paper address the significant issue of closing the loop between professional development, transfer of learning, and implementation. This paper is relevant to teachers, academic leaders, and developers who are interested in professional and career development, and in closing the loop and assurance of learning.